Efecto inhibitorio de extractos de renealmia alpinia rottb. maas (Zingiberaceae) sobre el veneno de bothrops asper (mapaná) (2012)
Introduction: Traditional medicine is an invaluable source of research into new medicines as a supplement for the treatment of snakebite, considered as a serious public health problem worldwide. The extracts of the medicinal plant, Renealmia alpina, have been used traditionally by indigenous people of Chocó (Colombia) against Bothrops asper snakebite, a snake responsible for the majority of snakebite accidents in Colombia. Objective: The ability of extracts of R. alpinia leaves was tested for its ability to neutralize the hemorrhagic, coagulant and proteolytic effects of the snakebite venom of B. asper. Materials and methods: The acute toxicity tests and analgesic activity of R. alpina were evaluated in vivo. In addition, tests were undertaken in in vitro conditions to demonstrate inhibition of coagulant, haemolytic and proteolytic activity of the B. asper venom. Results: Renealmia alpinia extracts had no toxic effects in experimental animals and also provided analgesic and antiophidian effects and protection against the lethal effects of the venom of B. asper. Conclusion: Renealmia. alpinia was an effective therapeutic alternative in association with antivenom treatment in the event of a B. asper snakebite accident. It was demonstrated to protect against the lethal effects and provided analgesic properties as well.